Management of Wet Age-Related Macular Degeneration: A Case Report - Handayani, Retno Tharra; H. A.K Ansyori; Ramzi Amin (Sriwijaya Journal of Ophthalmology, 2024)
Introduction: Age-related macular degeneration (AMD) is a progressive neurodegenerative disease of the photoreceptors and retinal pigment epithelium (RPE). It is a leading cause of blindness and visual impairment in the elderly population, despite recent advances in treatment. We reported a case of wet AMD and its management. Case Presentation: A 69 years old woman complained of blurred vision, especially in the left eye, which she had experienced since 3 years ago, progressively worsen since the last 3 months. Fundoscopy and OCT examination was done. Fundoscopy found no foveal reflex with a drusen and perifoveal haemorrhage found on left eye. She was diagnosed with wet age-related macular degeneration type II of left eye. She had done intravitreal anti-VEGF injection with local anaesthesia. Conclusion: AMD management relies heavily on observation, lifestyle changes, frequent follow-up evaluations, early recognition of visual impairment and detection of CNV. Meanwhile, the current modality for wet AMD therapy is intravitreal anti-VEGF injection to preserve patient’s visual acuity and improve quality of life.